Damage Investigation in A319 Aluminium Alloy by X‐ray Tomography and Digital Volume Correlation during In Situ High‐Temperature Fatigue Tests. (6th July 2016) - Dahdah, N.; Limodin, N.; El Bartali, A.; Witz, J. F.; Seghir, R.; Charkaluk, E.; Buffiere, J. Y.
Abstract: The aim of this work is to analyse the strain field heterogeneity in an aluminium alloy subjected to low‐cycle fatigue at high temperature. In the cylinder heads produced by a lost‐foam casting process, the microstructure of the studied alloy consists hard intermetallic phases and large gas and microshrinkage pores. In order to study the influence of this complex 3D microstructure on fatigue crack initiation and propagation at 250 °C, an experimental protocol using laboratory and synchrotron tomography, finite element simulation and a new digital volume correlation platform have been used. The results showed the role of pores in the crack nucleation and highlighted the importance of hard phases in the crack propagation, thanks to the resolution on the DVC measurement.